Deciphering the role of epigenetics in plant pathogen resistance: Strategies for sustainable sugarcane management - Faisal Mehdi; Yuanli Wu; Shuzhen Zhang; Yimei Gan; Zhengying Cao; Shuting Jiang; Limei Zan; Benpeng Yang (Plant Stress)
Sugarcane, an important cash crop, is facing increasing threats to its sustainability from various biological stressors. Despite its economic importance, the complex molecular mechanisms involved in sugarcane's defense against pathogens especially the role of epigenetic regulators are not well understood. This review explores how epigenetic regulators contribute to sugarcane's defense mechanisms. It examines the functions of pathogenesis-related (PR) proteins and their interactions with epigenetic modifications. Under normal conditions, plants adjust their gene expression in response to pathogenic threats. Specific transcription factors are activated by external stimuli, which then enhance the expression of defense-related genes. Epigenetic mechanisms, such as histone modifications and DNA methylation, regulate these gene expressions related to biotic stress responses. Additionally, chromatin remodelers and non-coding RNAs work together to boost plant defenses, improving resistance and productivity in various environmental conditions. Importantly, these epigenetic processes create a form of environmental memory and priming, enabling plants to adapt to new challenges based on past experiences. This review offers a comprehensive overview of current knowledge regarding the epigenetic mechanisms that support sugarcane's defense against pathogens. It provides detailed insights into the complex interactions between plants and fungi and discusses innovative crop improvement strategies aimed at improving disease resistance and overall crop resilience. By clarifying these molecular pathways, the review lays a foundation for future research that seeks to strengthen sugarcane against biotic stressors and ensure the sustainability of sugar and bioenergy production.